Magnetism in monolayer 1T-MoS2 and 1T-MoS2H tuned by strain. Issue 15 (23rd February 2018) - Xu, Wei; Yan, Shiming; Qiao, Wen
Abstract : The magnetic properties of 1T-MoS2 and 1T-MoS2 H subjected to equiaxial tensile strain are calculated using density functional theory. Abstract : The magnetic properties of 1T-MoS2 and 1T-MoS2 H subjected to equiaxial tensile strain are calculated using density functional theory. It is shown that in a strain-free state, 1T-MoS2 and 1T-MoS2 H both exhibit magnetic behavior; as the strain increases, their magnetic properties show an increasing trend. This shows a significant difference from those of 2H-MoS2 and 2H-MoS2 H. Based on Crystal Field Theory, the magnetic generation and variation of 1T-MoS2 and 1T-MoS2 H are explained in this paper. The good tunable magnetic properties of 1T-MoS2 and 1T-MoS2 H suggest that they could be applied as a spin injection source for spin electronics.